2021
DOI: 10.23937/2469-5858/1510124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music-Based Physical Training on Selected Motor and Cognitive Abilities in seniors with Dementia-Results of an Intervention Pilot Study

Abstract: Background:The relevance of the treatment of dementia will increase significantly in the coming years. Although studies show that exercise and music produces positive effects on motor function and cognition in people with dementia, the preferred treatment for dementia is medication. Therefore, research into non-pharmacological treatment is important. There are first indications that the combination of music and physical exercise positively influence cognitive and motor skills. Our aim was to examine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It comprises a three-stage frame of the upper, middle, and lower parts; therefore, it is capable of whole-body exercise in various directions. Body spider was also used to confirm the effects of exercise in older adults [ 34 ]. The experimental group performed a dual-task resistance exercise program to improve cognitive function, and the control group performed a resistance exercise program for the same period using the same equipment (Table 1 ; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It comprises a three-stage frame of the upper, middle, and lower parts; therefore, it is capable of whole-body exercise in various directions. Body spider was also used to confirm the effects of exercise in older adults [ 34 ]. The experimental group performed a dual-task resistance exercise program to improve cognitive function, and the control group performed a resistance exercise program for the same period using the same equipment (Table 1 ; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Higuti et al (2021) reported listening to music and practicing physical exercise for 12 weeks; one session per week (25-30 min) did not significantly change functional or cognitive performance in institutionalized older adults with dementia (Higuti et al, 2021). In contrast, some studies that have used more frequency (twice a week) and duration (one hour) of exercise and music sessions reported improvements in cognitive, psychological, and motor abilities in patients with mild to moderate dementia (Satoh et al, 2014(Satoh et al, , 2017Prinz et al, 2021). Therefore, a combination of music therapy and exercise as dual-task training can be an excellent option to improve AD patients' physical and cognitive fitness.…”
Section: Introductionmentioning
confidence: 99%